Ochrona prawna zaufania przez informację przy świadczeniu usług finansowych: [Legal protection of trust by information in financial services provision] (Studia Prawnicze / The Legal Studies, 2015)
Problematyka ochrony zaufania na rynku usług finansowych jest zagadnieniem o niezwykle doniosłym znaczeniu, co znajduje odzwierciedlenie we współczesnym prawie, zarówno unijnym, jak i krajowym. Usługi finansowe stanowią w istocie produkty zaufania, co oznacza, iż ocena ich właściwości, stosunku jakości do ceny, ryzyka łączącego się z zawarciem umowy stają się znane nabywcy, w szczególności nieprofesjonalnemu dopiero po zawarciu umowy. W okolicznościach takich podmiot nieprofesjonalny zmuszony jest działać w zaufaniu do informacji przekazywanej mu przez instytucję finansową, a niedostarczenie nabywcy wymaganej informacji lub przedstawienie ich w sposób nieprzejrzysty prowadzić może do występowania zakłóceń w efektywnym funkcjonowaniu mechanizmów rynku, na którym cena usługi odzwierciedlać powinna informację dotyczącą jej jakości i ryzyk z nią związanych. Legal protection of trust in the area of financial services is a very important subject, which finds reflexion in contemporary law, both European as well as national one. Financial services constitute, as a matter of fact, products of trust, which means that the evaluation of their properties, the relation of the quality to the price, the risk resulting from concluding the contract become known to the non-professional buyer after concluding the contract. In such circumstances, the non-professional party is forced to act in trust to the information received from the financial institution, and failure to provide the buyer with the obligatory information or providing it in an non-transparent form may lead to appearance of disturbances in the efficient functioning of market mechanisms, on which the price of the service should reflect the information about its quality and risks connected with it. The article provides an insight into the area of trust and precontractual information duties as an institution addressed to protect parties’ trust one to another. The scope of the article covers the area of financial services, in particular credit and investments.